1995
DOI: 10.1523/jneurosci.15-02-00957.1995
|View full text |Cite
|
Sign up to set email alerts
|

FORSE-1: a positionally regulated epitope in the developing rat central nervous system

Abstract: We designed a protocol to identify cell surface molecules expressed in restricted spatial patterns in the developing central nervous system (CNS) that might be regulated by regionally restricted transcription factors. The immunogen was a membrane fraction from NT2/D1 embryocarcinoma cells that were induced to differentiate into neurons and upregulate Hox gene expression in response to retinoic acid. One monoclonal antibody (mAb), FORSE-1, specifically labels the rostral rat CNS from the earliest stages. Staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…7A, arrows). This discontinuous ventricular expression pattern is very similar to that reported previously with monoclonal antibodies 7A in the mouse (29) and FORSE-1 in the rat (30). Both antibodies recognize fucosylated neolacto-glycolipids bearing Lewis-X structures (3Ј-fucosyllactosamine), which are the predominant carriers of the Lewis-X determinant in the embryonic rodent cortex.…”
Section: Resultssupporting
confidence: 86%
“…7A, arrows). This discontinuous ventricular expression pattern is very similar to that reported previously with monoclonal antibodies 7A in the mouse (29) and FORSE-1 in the rat (30). Both antibodies recognize fucosylated neolacto-glycolipids bearing Lewis-X structures (3Ј-fucosyllactosamine), which are the predominant carriers of the Lewis-X determinant in the embryonic rodent cortex.…”
Section: Resultssupporting
confidence: 86%
“…2H). These results are compatible with data in mouse development where Forse1 predominantly marks forebrain precursor cells (Tole et al 1995).…”
Section: Forse1 As a Marker For The Prospective Isolation And Clonal supporting
confidence: 92%
“…Cultures of early hESC-derived neural rosettes are not homogenous and can contain differentiated neurons, neural crest deriva-tives, nonneural derivatives, or undifferentiated hESCs. Forse1 was originally isolated as an antibody recognizing a surface epitope expressed in neuroepithelial cells derived upon RA-induction of the human embryonal carcinoma cell line NT2D1 (Tole et al 1995). A recent study reported Forse1 expression in a subset of hESCderived neural progeny (Pruszak et al 2007).…”
Section: Forse1 As a Marker For The Prospective Isolation And Clonal mentioning
confidence: 99%
“…FORSE-1 is an antibody that recognizes a specific, as-yet-undefined configuration of the Lewis X glycan (15). In rat embryos, FORSE-1 stains the anterior portion of the neural tube and developing brain, and its epitope appears to be primarily present on two neutral glycolipids (37).…”
Section: Discussionmentioning
confidence: 99%